The Mandatory 4 Years Desludging Frequency of Underground Septic Tanks in Residential Areas: A Case Study in Sibu Sarawak, East Malaysia - Wen Kam Leong; Alex Lung Keat Ngo; Alvin Choon Hsien Wong; Jen Hua Ling; How Teck Sia (Journal of the Civil Engineering Forum, 2022)
Underground septic tanks are the most common and conventional primary black water treatment adopted by local households in Sarawak. To ensure its usefulness, periodic mandatory desludging or emptying of the various types of rateable holdings was enforced from 1998. The current mandatory desludging frequency is 4 years for residential households, although its effectiveness is still not clear, substantial annual finance and subsidies are being allocated by the Sarawak State Government. In this study, the underground septic tanks in Sibu located in residential areas in Sarawak, East Malaysia, were evaluated quantitatively based on the measured faecal sludge with a known retention time in respect to the regulated desludging frequency. Furthermore, various problems were encountered during the initial measurement carried out by sludge judge which typically used by the wastewater treatment and chemical plants. A modified PVC pipe was proposed to overcome these observed problems. This has greatly improved the measurement time and substantially reduced unwanted impediments for the contractor during desludging. The back analysis results showed that the recommended desludging frequency based on the ratio of total sludge and scum to the effective working volume in 30% and 50% thresholds for residential areas were 3.82 and 6.36 years, respectively. Furthermore, it was discovered that there was a potential to adjust the existing mandatory 4 years desludging frequency to a longer period for cost-effective consideration. This study is strictly on the physical quantity measurement of sludge and scum volumes for the known retention times. The complex influences of microbiological activities, micro-environmental factors and sizes or geometries of septic tanks for faecal sludge production were not considered.